Chemical evolution of the Paleoproterozoic Rooiberg Group Kaapvaal Craton South Africa : new insights into the formation of a silicic large igneous province (SLIP) - Lenhardt, Nils (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.